Comparing Factors Influencing Loyal Consumption Behavior Towards Fast-Food Restaurants - Singh, Ajwinder; Nanda, Parul (Indian Journal of Marketing, 2022)
Facing saturation back home, many global fast-food restaurants have enhanced their presence across tier 2 and tier 3 cities in India to increase their market. The factors that propelled this buoyancy include rapid urbanization, changing lifestyles, less switching costs, and a rise in annual middle-class spending, which has made this sector highly competitive for retaining customersâ€™ loyalty. A comparative study of three fast-food multi-national brands was conducted to evaluate service performance vis-Ã -vis customer preference to predict the basis of loyal consumption behavior. For measuring the service performance, two MCDM approaches were integrated with SERVQUAL methodology, that is, AHP & TOPSIS. The paper involved the identification of service quality dimensions and sub-dimensions relevant to fast-food service and then generating weights using the AHP technique, and then finally, establishing the ranking using TOPSIS. The findings revealed that food quality, timely service, clean and hygienic environment, availability of all menu items, consistency of taste, price sensitivity, friendly dealing, and soothing ambiance are the factors that bring loyal consumption behavior.